TULLUPAMPAY: ETHNOGRAPHIC DESCRIPTION OF A RITUAL IN TRIBUTE TO DEAD IN MANTARO VALLEY, JUNIN - Perales Munguía, Manuel F. (2011)
We report on a ritual referred to as Tullupampay that is performed in the village of Chongos Bajo, southeast of the modern city of Huancayo in the central highlands of Peru. First, we present basic data about the place where this cultural practice occurs, as well as a description of the different activities carried out in Chongos Bajo during the celebration of Día de Todos los Santos (All Saints’ Day). After that we describe the ceremony of Tullupampay in detail, including the Catholic Mass. Interestingly, many of the people who participate in the ritual take the skulls of deceased persons that they keep their homes with them to this Mass. Finally, we outline a general picture about the popular beliefs surrounding the “little ghosts” whose skulls are venerated by the local people, followed by some thoughts regarding the theoretical relevance of the study of the cultural phenomena in the field of anthropology of religion.